PENGARUH PENGALAMAN KERJA DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN PADA PT. BERKAT UTAMA NUANSA TANJUNG MORAWA - ny, Hen; jella, En; Luhur, Michael; Gunarsih, Inggriani; Setyohadi Wijaya, Koko (Aksara Public, 2019)
The research method used the quantitative approach, a type of research was the quantitative descriptive, the nature of research was the explanatory. The methods of data collection were the interview, questionnaire and documentation study. The method of analysis was multiple linear regression by testing classical assumption, namely normality, multicollinearity and heteroscedasticity. The population in this research were 65 employees of PT. Berkat Utama Nuansa, samples taken sampling saturated, namely 30 from PT. NESS Jl. Besar Namorambe No. 70 Kel. Namo Mbelin Kec. Namo Rambe tested the validity and reliability. The results of the research on the hypothesis showed that the work experiences and work satisfactions simultaneously (Test F) had a positive effect to employees performance with a value of 73.866. Partially (Test t) the work experiences had a positive effect with a value of 8,003 and the work satisfactions had a positive effect with a value of 0,387 to the employees performance. The result of determination coefficient test (R Square) obtained Adjusted R Square of 0,695 showed that the work experiences and work satisfaction affect to the employees performence with a percentage rate of 69,5% while the remaining 30,5% were other factors not examined by the researcher